Surface Ocean Current Variability Near Selayar Island During the Three El Niño-Southern Oscillation (ENSO) Phases - Andika, Andika; Warouw, Gladiva (JURNAL GEOCELEBES, 2026)
This study investigates the seasonal and interannual variability of surface ocean currents around Selayar Island, Indonesia, with a focus on differences among the three phases of the El Niño–Southern Oscillation (ENSO). Monthly surface current data from 1993 to 2020 were analyzed using climatological, composite, and anomaly approaches. The results reveal a spatially heterogeneous current structure that is dominated by seasonal variability, with domain-averaged current magnitudes ranging from approximately 0.085–0.305 ms-1. Interannual variability related to ENSO is evident mainly in the magnitude of surface current anomalies, which range approximately 0.03–0.05 ms-1 during El Niño and increase to about 0.07–0.09 ms-1 during La Niña, with peak values reaching ~0.10–0.12 ms-1. This indicates that ENSO primarily modulates current intensity rather than flow direction. Differences in anomaly direction are more pronounced under Neutral conditions, where anomaly patterns differ from those observed during both El Niño and La Niña phases. Overall, the results indicate that ENSO acts as an interannual modulation of surface currents, while monsoonal forcing remains the primary control on surface current dynamics in the study region.